MANAGEMENT OF INNOVATIVE DEVELOPMENT OF ENTERPRISES IN THE CONTEXT OF A CHOICE OF ENERGY SECURITY STRATEGY - Oksana Mykoliuk; Nataliia Prylepa (Сучасний стан наукових досліджень та технологій в промисловості, 2018)
The subject matter of the research in the article is the energy security strategy of enterprise, the choice of which for the enterprise is the basis of full functioning, further economic and innovative development. The goal of this article is to identify the conditions and criteria of a choice of energy security strategy of enterprises taking into account the factors and threats of the internal and external environment. In the article we used such methods and techniques of scientific cognition: methods of analysis and synthesis – to consider the essence of energy security strategy, method of theoretical generalization – to identify the formation stages of energy security strategy of enterprise in the conditions of innovative development, a taxonomy-analytical method – to classify the main components of the energy security strategy management of enterprise, method of logical generalization – to justify the relevance of the topic, goals and objectives of the research, method of transition from abstract to concrete – in the formulation and justification of proposals for the selection of energy security strategy in the conditions of innovative development of the enterprise. Tasks: to determine the choice of alternative strategic perspectives of energy security; to analyze the main approaches to formation of energy security strategy in the conditions of innovative development; to develop scientific and methodological recommendations for neutralization of threats of the energy strategy of enterprise in internal and external environment, revealed in innovation development process. The following results were obtained: defined the main selection criteria of energy security strategy of enterprise; the author’s interpretation of the concept "energy security strategy of enterprise" is proposed, which is based on the vector of innovative development of enterprise in the field of energy security, which is aimed at rational and efficient use of energy and natural energy resources for achievement of strategic innovation aimed goals of energy policy; a structure for the energy security monitoring of enterprise has been formed and the main tasks of the enterprise’s energy security subdivision have been defined. Conclusions. Management of innovative development of the enterprise involves the development and implementation of the concept, which is the basis for the formation of the enterprise economically grounded policy of improving the competitiveness of the enterprise. The dynamism and uncertainty of the market economy requires management of the enterprise quick adaptation to changing environmental conditions. Achievement of effective functioning of socio-economic systems is possible on the basis of efficiency and focus on reducing energy consumption of the enterprise. Consequently, management of innovative development of the enterprise which is based on energy security, may be the only way for domestic enterprises, which will provide a significant increase in competitiveness and form a new management paradigm in the long term.